École, savoirs et valeurs : une tentative d’éclaircissement - Alain Beitone; Estelle Hemdane (Éducation et Socialisation)
The question of taking into account values in the educational institution is a major issue nowadays. Educating citizens, teaching them to have an ecologically aware behavior, promoting equality between girls and boys, etc…, are as many missions as the school system is charged to take on. First we will wonder about the choice of values we have to pass on and the risks of moral paternalism. Secondly, we will point out the necessary distinction between facts and values using the recent works of Habermas in particular. Thirdly, we will demonstrate that taking into account the values within schools is rightful, provided that dogmatism, militancy and cognitive relativism are rejected.